1995
DOI: 10.1159/000106920
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease and Associated Patterns of Memory Decline

Abstract: The relationship between chronic obstructive pulmonary disease (COPD) and cognitive functioning was analyzed in a study with 50 aging patients. A complex pattern of interactions was identified between emotional and cognitive functioning and chronic respiratory disease when the effects of age, sex, type and severity of disease were controlled. These patients did not show any global and diffuse cognitive impairment. Only a portion of COPD patients (about 30%) evidenced memory impairment which was confined to imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 6 publications
0
21
1
1
Order By: Relevance
“…Given that over 50% of hospitalised patients with COPD have coexistent vascular disease [60], it is likely that this will influence cognitive function. However, the pattern of cognitive dysfunction in COPD has been shown to be different to that found in multiinfarct dementia [18], and memory has been shown to be worse in subjects with chronic cerebrovascular disease than in those with COPD [61]. Therefore, it is unlikely that cognitive dysfunction in COPD is due to vascular comorbidity alone.…”
Section: Cognitive Function In Vascular Disease and Other Comorbiditiesmentioning
confidence: 97%
“…Given that over 50% of hospitalised patients with COPD have coexistent vascular disease [60], it is likely that this will influence cognitive function. However, the pattern of cognitive dysfunction in COPD has been shown to be different to that found in multiinfarct dementia [18], and memory has been shown to be worse in subjects with chronic cerebrovascular disease than in those with COPD [61]. Therefore, it is unlikely that cognitive dysfunction in COPD is due to vascular comorbidity alone.…”
Section: Cognitive Function In Vascular Disease and Other Comorbiditiesmentioning
confidence: 97%
“…Several studies found impairments in memory functions [43,44,48,49,54,56,59] and in higher cognitive functions [46,52,59,60]. The findings of Grant et al [47] suggested that the degree of hypoxemia contributed to test performance impairment.…”
Section: Cognitive and Neuropsychological Functioningmentioning
confidence: 99%
“…Physical activity has been associated with increased pulmonary capacity and has hence been hypothesised to protect against cognitive impairment and decline via various physiological mechanisms [13][14][15][16][17]. The disease factors thought to influence cognitive function via pulmonary function include asthma, chronic obstructive pulmonary disease [18][19][20][21], and sleep disorders [22,23].…”
mentioning
confidence: 99%